Quantification of Trace Mercury in Water: Solving the Problem of Adsorption, Sample Preservation, and Cross‐Contamination. Issue 1 (11th November 2019) - Zhang, Jingqi; Chao, Jingbo; Tang, Yang; Wan, Pingyu; Yang, Xiao Jin; Wong, Choon; Bruce, Mark; Hu, Qing
Abstract: Adsorption, sample preservation, and cross‐contamination are the major impediments to the accurate and sensitive analysis of low‐level mercury samples. Common measures to deal with this issue are to use Teflon, quartz, or borosilicate glass bottles for sampling, standard solution and sample preservation with oxidative chemicals, to prepare standard solutions daily and to use dedicated glassware. This paper demonstrates that these measures are neither efficient nor effective. Two common laboratory sample containers (borosilicate volumetric glass flasks and polypropylene tubes) are investigated for the preparation and preservation of water samples and standard solutions of 0.2–1 µg L −1 with 2% HNO3 . Mercury adsorption rates of 6–22% are observed within 30 min and after 48 days, the adsorption is greater than 98%. In stark contrast, no adsorption is found during a testing period of 560 days when the solutions are subject to potassium permanganate‐persulfate digestion. New glass flasks and polypropylene bottles are free of mercury contamination but reused flasks are a major source of mercury cross‐contamination. To minimize adsorption and cross‐contamination, standard solutions are treated by potassium permanganate‐persulfate or BrCl digestion, and each individual sample and standard solution should be stored and prepared in single‐use polypropylene bottle, without transference. Abstract : Adsorption and cross‐contamination are the major challenges for accurate analysis of trace mercury. This study demonstrates that adsorption is the root cause for cross‐contamination, and single use of polypropylene plastic bottles for sample preparation and storage is highly efficient to completely solve these notorious problems as long as sample and standard solutions are subject to potassium permanganate‐persulfate digestion.